1990
DOI: 10.1126/science.2111585
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Coagulation Factor XI a -Inhibitor, a Form of Alzheimer Amyloid Precursor Protein

Abstract: An inhibitor of coagulation factor XIa was purified from serum-free conditioned medium of HepG2 liver cells. Platelets stimulated with thrombin or calcium ionophore (A23187) secrete a protein functionally and immunologically identical to the inhibitor, implying a role for this inhibitor in hemostasis. Analysis of the amino-terminal amino acid sequence and immunologic reactivity showed the inhibitor to be a truncated form of the Alzheimer's amyloid precursor protein that contains a Kunitz-type serine protease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
166
0
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(174 citation statements)
references
References 28 publications
5
166
0
3
Order By: Relevance
“…PNII is a protease inhibitor that forms SDS-resistant inhibitory complexes with epidermal growth factor-binding protein, the ␥-subunit of nerve growth factor, and trypsin. Smith et al (25) reported that an inhibitor of coagulation factor XIa purified from the serumfree conditioned medium of HepG2 liver cells is also a secreted form of APP. Truncated forms of APP are derived from their cognate membrane-associated forms by proteolysis and have apparently lost the cytoplasmic and the transmembrane domains (26).…”
Section: Discussionmentioning
confidence: 99%
“…PNII is a protease inhibitor that forms SDS-resistant inhibitory complexes with epidermal growth factor-binding protein, the ␥-subunit of nerve growth factor, and trypsin. Smith et al (25) reported that an inhibitor of coagulation factor XIa purified from the serumfree conditioned medium of HepG2 liver cells is also a secreted form of APP. Truncated forms of APP are derived from their cognate membrane-associated forms by proteolysis and have apparently lost the cytoplasmic and the transmembrane domains (26).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme cleaves the /IAPP intracellularly (for review, see Checler, 1995) or nearby the external membrane (Sisodia, 1992), thereby liberating APPa, the putative physiological role of which has been well documented (Oltersdorf et al, 1989;Saitoh et al, 1989;Smith et al, 1990;Mattson et al, 1993;Qiu et a!., 1995). Most important is the observation that the site of a-secretase cleavage on /IAPP occurs in the middle of the A/I sequence and therefore likely precludes the formation of this amyloidogenic product.…”
Section: Discussionmentioning
confidence: 99%
“…This protein, also known as protease nexin 2, contains a Kunitz serine protease inhibitor domain (sequence shown in red in Fig. 1B), which has been found to strongly inhibit trypsin as well as several enzymes of the coagulation system (23,24). In the mesotrypsin-treated sample, the 120 kDa band is depleted, whereas two newly appearing bands with apparent molecular mass of ϳ40 and ϳ65 kDa were found by trypsin digestion and nanoLC-MS/MS to represent cleavage fragments of APP.…”
Section: Identification Of App As a Mesotrypsinmentioning
confidence: 99%
“…In normal biology, a variety of functions for APP have been implicated. The earliest to be described was the function of the secreted ectodomain of APP (sAPP) as protease nexin 2, a serine protease inhibitor that targets coagulation factor XIa (FXIa) with high specificity (23,24). This inhibitory activity has been localized to the Kunitz domain of sAPP (25).…”
mentioning
confidence: 99%